Development of a Sustainable Fashion Mobile Application Prototype Using Rule-Based Filtering Approach - Nila Natalia; Zahra Ramadhani Putri; Irfan Nafis Sjamsuddin (Deparment Information System, Siliwangi University, 2026)
Abstract— Rapid growth in the fast fashion industry has increased consumer behavior, especially among college students. This growth led to a surge in textile waste. This study aims to design and develop a mobile application prototype named